2001
DOI: 10.1007/s002310000146
|View full text |Cite
|
Sign up to set email alerts
|

On thermal boundary layer of a non-Newtonian fluid on a power-law stretched surface of variable temperature with suction or injection

Abstract: Heat transfer characteristics of a non-Newtonian uid on a power-law stretched surface of variable temperature with suction or injection were investigated. Similarity solutions of the laminar boundary layer equations describing heat transfer and¯uid¯ow in a quiescent uid were obtained and solved numerically. Velocity and temperature pro®les as well as the Nusselt number, Nu, were studied for two thermal boundary conditions; uniform surface temperature and variable surface temperature, for different parameters; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…In Figure 5 there is shown the variation of the skin friction with the power of the stretching velocity. It is an interesting dependence, not yet presented in the papers dealing with this subject, at our best knowledge:Our curves labeled with m =1 (linear stretched surface) in Figure 5 shows the same behavior, not only for impermeable surface (Tashtoush et al , 2001), but also for suction and injection.One remarks also the increase of S with m for any kind of fluids, but clearly those with n <1 are more affected by the intensification of the stretching. For these fluids the curves are almost linear and this direct proportionality between skin friction and power of stretching is a new interesting finding.The effect of injection to increase the skin friction as compared to the impermeable plate is the same as discussed for previous figures.The velocity profiles shown in Figures 6‐8 support a feature already reported in the literature, namely that the momentum boundary layer thickness decreases with increase in the power‐law index, see for instance Prasad et al (2009).…”
Section: Numerical Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…In Figure 5 there is shown the variation of the skin friction with the power of the stretching velocity. It is an interesting dependence, not yet presented in the papers dealing with this subject, at our best knowledge:Our curves labeled with m =1 (linear stretched surface) in Figure 5 shows the same behavior, not only for impermeable surface (Tashtoush et al , 2001), but also for suction and injection.One remarks also the increase of S with m for any kind of fluids, but clearly those with n <1 are more affected by the intensification of the stretching. For these fluids the curves are almost linear and this direct proportionality between skin friction and power of stretching is a new interesting finding.The effect of injection to increase the skin friction as compared to the impermeable plate is the same as discussed for previous figures.The velocity profiles shown in Figures 6‐8 support a feature already reported in the literature, namely that the momentum boundary layer thickness decreases with increase in the power‐law index, see for instance Prasad et al (2009).…”
Section: Numerical Resultssupporting
confidence: 65%
“…Comparisons with Tashtoush et al (2001) on the skin friction behavior are not possible since they did not report such results. However, in Prasad et al (2009) there is found that the skin friction decreases as the power-law index n increases (their Table II) and this is also our conclusion (for m ¼ 1 in Figure 3).…”
Section: Numerical Resultsmentioning
confidence: 90%
See 3 more Smart Citations